Barriers to, and facilitators of, education for children with disabilities worldwide: a descriptive review - Bani Odeh, Kifah; Lach, L. M. (Frontiers in Public Health, 2024)
Inclusionary ideals regarding the education of children with disabilities (CWD) are articulated in various international human rights treaties and instruments such as the United Nations Convention on the Rights (2006), the Salamanca Statement (1994), and the 2030 agenda of the UN’s Sustainable Development Goals (SDGs). In the latter, the fourth goal explicitly focuses on the removal of barriers to education and supporting access to quality, equity, and inclusion for people with disabilities. Although data regarding access to education among CWD remains scarce, it is well known that rates of their participation in education remain low, particularly among those in LMICs. The research question of this descriptive review is what are the barriers to and facilitators of education for children with disabilities worldwide aged between 6-18 years old? Methods : A descriptive review of literature published in English between 2013 and 2021 was conducted following the Joanna Briggs Institute (JBI) guidelines for a scoping review using the following databases: EBSCO, SocINDEX with full text (EBSCO), and ERIC (EBSCO). The search resulted in 7,072 titles and abstracts, which were narrowed down to 1,335 papers for full text review. After data extraction, 54 papers were included in the analysis, with 34 being qualitative, 10 quantitative, and 10 mixed-methods studies. The findings on the facilitators and barriers to education for children with disabilities were analyzed using the International Classification of Function, Disability and Health (ICF) and Urie Bronfenbrenner's Ecological Framework (1979). Out of the eligible studies included in our research, 40 were conducted in developing countries, while14 studies conducted on LMICs. Of the five environmental domains in the ICF, the most significant barriers were found to be that of attitudes and services, while technology and effective communication with school staff were found to play a crucial role in facilitating the education process. Applying Bronfenbrenner’s framework, barriers occurred at the micro-system (school level), meso-system (parent and teacher communication), exo-system (services), and macro-system (education policy). Only 3 out of the 54 studies included the voices of CWD. Despite documented barriers, facilitators of education for CWD are underexplored, lacking research on their voices. Further investigation is needed.